Analytical hierarchy process model to optimize the location of an industrial plant - Salas Bacalla, Julio Alejandro (2014)
The location of an industrial plant, is the process of choosing a geographical location to perform the operations of a company. To determine the best location, you must perform an assessment of the factors affecting the selection. Two groups of factors are considered: Quantitative, which are easy to quantify and Qualitative that are less tangible, hard to quantify, evaluation of the latter depends on the judgment of the analyst, keeping a tinge of subjectivity, making no model used to ensure that the venue is optimal. To optimize the classification of factors, it is proposed to use the model of Analytic Hierarchy Process (AHP) with a proper rating scale, which ensures consistency of it and allows the use of a software (Expert Choice). This study presents and demonstrates the contribution of the Analytic Hierarchy Process (AHP) in the task of optimizing the location of an industrial plant, compared with other methods.